The last economic plan of the first cycle of Raúl Alfonsín's government (1983-1985): tensions, contradictions and permanent instability (Res Gesta, 2023)
The Economic Plan of Bernardo Grinspun (1983-1985) developed as the first economic strategy during the government of Raúl Alfonsín (1983-1989) was less studied compared to the Austral Plan formulated from 1985. Although the Keynesian strategy of the Prime Minister of Economy It was brief, it still constitutes a vacant field to understand how the economic challenges were addressed from the government. With the aim of contributing to its knowledge, the work addresses the Argentine Economic Plan of December 1984, formulated jointly between the Ministry of Economy and the Central Bank in the framework of the closing of an agreement with the International Monetary Fund for foreign debt. Contrasted with journalistic, bibliographical sources, memoirs and other institutional documents of the time, we maintain that said program shows the contradictions, debates and tensions inherent to the national economic policy as weaknesses in the medium-term macroeconomic strategy.
Keywords: External debt; inflation; Central Bank; macroeconomy